Epstein-Barr virus receptor of human B lymphocytes is the C3d receptor CR2. - Fingeroth, J D (1984)
Identity of the Epstein-Barr virus (EBV) receptor with the complement receptor type 2 (CR2) was established in three sets of experiments using the monoclonal antibodies, HB-5 and anti-B2, which recognize a Mr 145,000 B-lymphocyte membrane protein that is CR2. First, the rank order for binding of fluoresceinated EBV to four lymphoblastoid cell lines (SB, JY, Raji, and Molt-4) was identical to the rank order for binding of HB-5 and anti-B2 by analytical flow cytometry. Second, pretreatment of cells with HB-5 followed by treatment with goat F(ab')2 fragments to mouse IgG blocked binding of fluoresceinated EBV on SB, a B-lymphoblastoid cell line. Virus attachment was not inhibited by HB-5 alone, second antibody alone, rabbit anti-C3b receptor, or UPC10 (an irrelevant monoclonal antibody). Third, transfer of CR2 from SB to protein A-bearing Staphylococcus aureus particles, to which HB-5 had been absorbed, conferred on them the specific ability to bind 125I-labeled EBV. We conclude that CR2 is the EBV receptor of human B lymphocytes.